Detection and identification of two Bartonella henselae variants in domestic cats in Germany. - Sander, A (1997)
To determine the prevalence of bacteremia caused by Bartonella henselae in domestic cats in the region of Freiburg, Germany, we investigated culture of blood from 100 cats from 89 different households over a 12-month period. B. henselae could be isolated from 13% (13 of 100) of these cats. In eight households with two cats each and in one household with three cats, B. henselae bacteremia was found either in all of the animals or in none of the animals. Positive cultures were more likely to be found for female, young (24 months of age or younger) cats than for male or older cats. Identification of the Bartonella isolates was made by colony morphology, by Gram staining, biochemically by RapID ANA II or Rapid ID 32 A systems, and by whole-cell fatty acid analysis. Differentiation between B. henselae and Bartonella quintana was only possible by 16S rRNA sequencing, enterobacterial repetitive intergenic consensus (ERIC)-PCR and sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Genomic fingerprinting of the B. henselae isolates by ERIC-PCR yielded two different patterns based on three distinct bands.